Get up and dance! [videorecording (DVD)] (PBS Kids, 2023)
Join the dance party with some of your favorite friends from PBS KIDS! Groove with Alma as she helps Eddie and Becka create a brand-new mash-up dance. Then Mr. Lion encourages Elinor and her pals to create their own dance routine, while Luna gives Leo a tango lesson, and much, much more!